Metabolic diseases in farm animals - Payne, Jack Marsh (Heinemann Medical Books, 1977)
Metabolic Diseases in Farm Animals discusses metabolic diseases in farm livestock, focusing on four clinical syndromes-parturient hypocalcaemia, hypomagnesaemia, ketosis, and bloat. This book discusses metabolic disorders associated with water, calcium, magnesium, sodium, potassium, nitrogen, and phosphorus. The parturient paresis, which causes considerable metabolic stress and disrupts the daily pattern of feeding and digestion of dairy cows is also elaborated. This text covers the changes in mineral metabolism at parturition; factors predisposing dairy cows to parturient paresis; cause of pa.